2021
DOI: 10.3748/wjg.v27.i15.1563
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of late complications with coverage agents in endoscopic resection of colorectal lesions: Current landscape in gastrointestinal endoscopy

Abstract: Endoscopic removal of large (≥ 20 mm) non-pedunculated colorectal lesions (LNPCLs) may result in major adverse events, such as delayed bleeding (DB) and delayed perforation (DP), despite closure of the mucosal defects with clips. Topical application of a coverage agent refers to the creation of a shield with a biocompatible medical device (tissue or hydrogel) with proven bioactive properties. Coverage of the eschar after endoscopic resection provides shielding protection to prevent delayed complications. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Coverage of the defects after endoscopic excision supplies shielding protection to prevent delayed complications (Figure 1B ). The above results confirm that the work done by Lorenzo-Zúñiga et al [ 1 ] is worthy of recognition and that our findings can serve as a complement to their research. In the future, we should re-evaluate the efficacy of prophylactic clipping of LNPCLs and further explore the role of coverage agents in preventing delayed adverse events.…”
Section: To the Editorsupporting
confidence: 92%
See 2 more Smart Citations
“…Coverage of the defects after endoscopic excision supplies shielding protection to prevent delayed complications (Figure 1B ). The above results confirm that the work done by Lorenzo-Zúñiga et al [ 1 ] is worthy of recognition and that our findings can serve as a complement to their research. In the future, we should re-evaluate the efficacy of prophylactic clipping of LNPCLs and further explore the role of coverage agents in preventing delayed adverse events.…”
Section: To the Editorsupporting
confidence: 92%
“…We agree with Lorenzo-Zúñiga et al [ 1 ], who reported that the conventional utilization of prophylactic clipping has not diminished the overall risk of postprocedural bleeding, and focus on the economic efficiency ratio is needed. A cohort study of 8366 colonoscopies involving polypectomy conducted by Forbes et al[ 3 ] yielded 95 delayed postpolypectomy bleeding (DPPB) incidents.…”
Section: To the Editorsupporting
confidence: 89%
See 1 more Smart Citation
“…The use of coverage agents to manage AEs related to EMR or endoscopic submucosal dissection has gained interest in recent years because it is the simplest and quickest method for covering large mucosal defects. Topical application of gels and powders provides shielding protection of the eschar and has proven efficacy in the prevention of CSPEB, especially in proximal lesions or when complete clip closure is not possible because of large size or poor accessibility (59,60).…”
Section: Coverage Agents: Gels and Powdersmentioning
confidence: 99%
“…While Cui et al detail a thermogel prepared from copolymers poly(D,L-lactide-co-glycolide)-b-poly(ethylene glycol)-b-poly(D,L-lactide-co-glycolide). 12,22,23 Each hydrogel shows significant clinical potential with testing in large animal models. Our interest lies in the use of a hydrogel dressing post polypectomy: a first-of-its-kind.…”
Section: ■ Introductionmentioning
confidence: 99%